p-tert-Butylthiacalix[4]arenes functionalized by N-(4’-nitrophenyl)acetamide and N,N-diethylacetamide fragments: synthesis and binding of anionic guests - Vavilova, Alena A.; Stoikov, Ivan I. (Beilstein Journal of Organic Chemistry, 2017)
New p-tert-butylthiacalix[4]arenes, which are mono-, 1,2-di- and tetrasubstituted at the lower rim containing N-(4’-nitrophenyl)acetamide and N,N-diethylacetamide groups in cone and partial cone conformations have been synthesized. Their complexation ability towards a number of tetrabutylammonium salts n-Bu4NX (X = F−, Cl−, Br−, I−, CH3CO2−, H2PO4−, NO3−) was studied by UV spectroscopy. The effective receptor for the anions studied as well as selective receptors for F−, CH3CO2− and H2PO4− ions, which based on the synthesized thiacalix[4]arenes, have been obtained. It was shown that p-tert-butylthiacalix[4]arene tetrasubstituted at the lower rim by N-(4’-nitrophenyl)acetamide moieties bonded to the anions studied with association constants within the range of 3.55 × 103–7.94 × 105 M−1. Besides, the binding selectivity for F−, Cl−, CH3CO2−, and H2PO4− anions against other anions was in the range of 4.1–223.9. Substituting one or two fragments in the macrocycle with N,N-diethylacetamide groups significantly reduces the complexation ability of the receptor. In contrast to the 1,3-disubstituted macrocycle containing two N-(4’-nitrophenyl)acetamide moieties, the 1,2-disubstituted thiacalix[4]arene, which contains only one such fragment and a N,N-diethylacetamide moiety, selectively binds F− anions.
Keywords: anion binding; synthesis; thiacalixarenes; UV spectroscopy